Effect of Cu addition on microstructure and mechanical properties of Fe–2 wt-%Ni alloy processed by metal injection moulding. (May 2014) - Husein, S.; Yang, H. W.; Kim, Y. G.; Gun Ko, Y.
Abstract : A study investigated the effect of Cu addition on microstructure and mechanical properties of Fe–2 wt-%Ni alloy fabricated by a metal injection moulding. Sintering treatments at 1100°C for 1 h were carried out on the present samples with various Cu contents of 0–3 wt-%. Microstructural observations revealed that, under the same sintering condition, both the size and volume fraction of the micropores increased as the amount of Cu content increased, which was attributed to the movement of Cu elements into the matrix boundaries during sintering. Some micropores appeared to be connected together when Cu content exceeded 2 wt-%. Despite a significant amount of the micropores present in the microstructure, values of microhardness increased due to the solid solution hardening associated with the Cu addition.